Factors associated with food security in Depok City, Indonesia during the COVID-19 pandemic: a cross-sectional study - Fatmah, Fatmah (Frontiers in Sustainable Food Systems, 2024)
The COVID-19 pandemic has considerably impacted food insecurity. The study aimed to assess the impact of the COVID-19 pandemic on food security and its related factors. Methods: The study employed a cross-sectional design, utilizing face-to-face interviews to collect data from 140 selected households using Simple Random Sampling. The study assessed the independent variables: socio-economic characteristics including parental age, maternal education, employment status, family type, number of biological children, family income, and food expenditure, with the food security level as the dependent variable. Family food security was determined through a modified version of the United States Family Food Security Survey Module-USDA, utilizing 15 of the original 18 questions. Binary Logistic Regression Analysis was employed to identify the dominant factor related to household food insecurity. Results and discussion: A significant proportion of families (66.4%) experienced food insecurity, where severe hunger was the most prevalent problem (25%). Parental age and employment, maternal education, family composition, number of biological children, income, total food expenditure, government social assistance, the impact of COVID-19 on the family, and percentage of food consumption to total spending (p < 0.001) significantly influenced family food security levels. The Binary Logistic Regression Analysis revealed that mothers over the age of 44 had a 9.9-fold increased likelihood of experiencing food insecurity compared to those under 35. Mothers with lower levels of education exhibited a 6.9-fold higher probability of food insecurity than those with moderate education. Families incorporating non-food expenses demonstrated a 23-fold greater risk of food insecurity than those without such expenditures. Families who received government social assistance were more at risk of food insecurity than those without such support. Thus, government social assistance played a critical role as a primary determinant factor for food security during the pandemic, with a probability of 45 times. Conclusion: Food security levels were influenced by various factors, including parental age and employment, maternal education, family composition, number of children, income, total food expenditure, government social assistance, and the impact of COVID-19 on the family. Government social assistance was essential during COVID-19 to enhance food security.